IMPLEMENTASI BACKWARD CHAINNING PADA SISTEM PAKAR UNTUK DETEKSI KERUSAKAN PADA LAPTOP BERBASIS WEB - Reny Wahyuning Astuti; Novhirtamely Kahar; Supriyanto (JURNAL AKADEMIKA)
All this time occor the increasing of interest in using computer for artificial intelligence. Artificial intelligence is activity that provides the machines such as computer with ability to show behavior is considered intelligent if it observed by human. One of Artificial intelligence is the expert system to detect the damage of laptop. The expert system is built by PHP programming lenguage, and using my SQL as database. Input data in this expert system are data of damage indication, kinds of damage data and the ways to repair, solution data, and user data. Input data will be processed to detect damage in laptop by using backward chaining and this system will provide output such as data of damage indication, kinds of damage, the ways to repair the damage and this data will be provide for user with the function the user can know damage in their laptop and also in order the user can repair the damage of laptop by theselves.